Comparison of Effectiveness of Precooling the Site of Injection Using Topical Ice and Topical Anesthetic Gel in Children Between 7- 12 Years- A Split Mouth Comparitive Study - Perumal, Sowmiya; Arumugam, Selvabalaji; Vasanthakumari A; Sankar, Dhivyashanthi; Venkatesan, Ramesh; Mahalakshmi, Shri (Journal of Neonatal Surgery, 2025)
Background: Topical anesthetics help alleviate fear, anxiety, and pain in pediatric dental treatments. Cryotherapy may enhance pain management by cooling the oral mucosa. This split-mouth study evaluates the efficacy of cryo-anesthesia versus a topical anesthetic gel during inferior alveolar nerve blocks. Aim: The aim of this study is to compare the effectiveness of topical ice and topical anesthetic gel in alleviating pain during local anesthesia administration in children aged 7 to 12 years. Materials and Methods: Fifty children requiring bilateral mandibular local anesthesia participated. Topical anesthetic gel (precaine) was applied on one side during the first visit, while cryo-anesthesia was used on the opposite side in the second appointment. Pain intensities were evaluated using a 100-mm visual analog scale and the sound, eye, and motor scale. Data was analyzed using paired t-tests. Results: VAS scores indicated significantly lower pain in the cryo-anesthesia group compared to the precaine group. Although SEM scores were lower for cryo-anesthesia, the difference was not statistically significant. Conclusion: Cryo-anesthesia effectively reduces pain during local anesthesia administration in children compared to topical anesthetic. Its advantages include pain reduction, quicker application, and avoidance of unpleasant taste.